A Technique Using a Low-Cost, Accessible Cannula to Aid Scaffold Passage in Dry Arthroscopic Cartilage Repair in the Knee - Andrew Chou, B.S., M.D., M.R.C.S. (Edin); Denny Lie, M.B.B.S., F.R.C.S., F.A.M.S (Arthroscopy Techniques, 2020)
Although autologous matrix-induced chondrogenesis has grown increasingly popular, it can be technically challenging to place the scaffold within the knee efficiently without extending the arthroscopic incisions. To facilitate arthroscopic placement of the matrix into the knee, we developed a technique that involves fashioning a cannula from a standard 5-mL syringe. This technique enables surgeons to conveniently and efficiently place the matrix through the standard arthroscopic ports at minimal cost.